Analisis Kinerja Sistem Kompresor Udara Botol Angin Sebagai Sumber Pembangkit Generator Di Laboratorium Engine Hall Politeknik Ilmu Pelayaran Makassar - Syahrisal Syahrisal (Jurnal Teknik Mesin Sinergi, 2021)
The compressed air supply device on the ship is auxiliary equipment used for starting the engine. The purpose of this study is to analyze the performance of the air compressor as a generator source in the Engine Hall laboratory. This study seeks to determine the performance of the compressor sistem as a generator drive in the Engine Hall Laboratory and the efficiency of the compressor sistem. The methodology used in this research is a quantitative method by calculating the performance of the compressor sistem as a generator, including compressors and wind bottles. The conclusion of this study is that the smaller the pressure exerted when compressing the air into the wind bottle, the smaller the mass of air that enters the wind bottle, likewise the greater the pressure exerted during compression, the greater the mass that enters the wind bottle (202, 65 kPa with an air mass of 1.0393 kg and 2431.8 kPa with an air mass of 12.162 kg). The smaller the pressure exerted when compressing the air to the wind bottle, the greater the mass flow rate of air in the tube (202.65 kPa with an air mass flow rate of 0.0297 kg/sec and 2431.8 kPa with an air mass flow rate of 0.0115 kg / sec). The greater the sistem output power, the greater the efficiency of the compressor sistem and the smaller the sistem output power, the smaller the efficiency of the compressor sistem (1000 Watt with an efficiency of 26.311% and 218 Watt with an efficiency of 5.742%).